The impact of user involvement in software development process - Nouf Bin saif; Mashael Almohawes; Nor Shahida Mohd Jamail (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
In software development process, user can take part in any phase of the process, depending on what model is being applied. Lack of user involvement can result in a poorly designed solution, or even a solution that conflicts with user’s needs. This review paper presents the impact of user involvement in software development process. In this study, different software development processes will be reviewed, show where the user usually gets involved in different models such as: Structural (Waterfall, V-model) and incremental (Scrum-extreme programming XP). As each model differs from the other, each of them has a different perspective of where user should take part and where they should not. This can be an asset that helps project managers, and leaders to develop suitable strategies to follow in their projects.